Synthesis of Ge-based one-dimensional nanomaterials for photodetector applications - Yan, Chaoyi (2011)
This thesis focused on the synthesis of Ge-based one-dimensional (1D) nanostructures for photodetector applications. We presented the comprehensive studies of controllable syntheses of Ge-based nanostructures, including Ge nanowires (NWs), zinc germanate (Zn2Ge2O4, ZGO) NWs and indium germanate (In2Ge2O7, IGO) nanostructures. Photodetector using those novel nanostructures were fabricated and studied, aiming to achieve high wavelength selectivity, high photoresponse time and low fabrication cost. GeNWs were synthesized in a horizontal high temperature furnace using both conventional Au and novel Bi catalysts. The growth conditions were carefully optimized to achieve the best NW yield. Morphology, crystal structure and chemical compositions of the NWs were characterized using various instruments. Photodetectors based on single GeNW and NW networks were fabricated and studied. Network devices with facile fabrication processes exhibited greatly enhanced photoresponse time than single NW devices and are considered as alternative solutions for further large scale production. Ternary